Control Method of Step Voltage Regulator on Distribution Lines with Distributed Generation - Jong-Bin Kim; Min-Gu Lee; Jung-Hun Lee; Je-Chang Ryu; Tae-Seong Choi; Min-Su Park; Jae-Eon Kim (Energies, 2022)
Generally, utilities regulate the voltage on the long power distribution line within a permissible range by using a step voltage regulator (SVR), which is located around the middle of the line and operates according to the condition of the line current. However, as large-scale distributed generations (DG’s) are interconnected into distribution lines, it is difficult to maintain the line voltage properly owing to bi-directional power flow or reverse power flow. Therefore, this paper proposes a novel SVR tap-changing algorithm to solve the problem, considering line load conditions and reverse power flow. Its validity is verified through the PSCAD/EMTDC software tool and simulations.